BIMBINGAN KELOMPOK DARING DENGAN TEKNIK SOSIODRAMA TERHADAP KEPERCAYAAN DIRI SISWA KELAS VII BERBANTUAN APLIKASI ZOOM MEETING - Salma Nur Fauziah; Rima Irmayanti (IKIP Siliwangi, 2022)
Self-confidence is an important component for adolescents in forming a person who has a good quality of life. In the process of development, adolescents are often faced with situations that make them experience a crisis of confidence. The purpose of this study was to find out how the implementation of online group guidance through sociodrama techniques on self-confidence in socializing class VII students. This research is a qualitative descriptive study with data collection methods by observation and interviews. The subjects taken in this study were 6 seventh grade students. The results of this study indicate that online group guidance through sociodrama techniques can increase students' self-confidence. In its implementation there are several obstacles faced, namely internal factors, namely from within students and external factors, namely from outside students such as network stability when using the Zoom Meeting application. Keywords:roleplaying, guidiance and counseling, self-confidence